Concurrent chemoradiotherapy with cisplatin or cetuximab for locally advanced head and neck squamous cell carcinomas: Does human papilloma virus play a role?. (August 2016) - Ou, Dan; Levy, Antonin; Blanchard, Pierre; Nguyen, France; Garberis, Ingrid; Casiraghi, Odile; Scoazec, Jean-Yves; Janot, François; Temam, Stephane; Deutsch, Eric; Tao, Yungan
Highlights: Concurrent CRT was associated with better PFS over BRT independent of p16 status. No difference of total late toxicity incidences was observed between the two groups. T and N classification, smoking status, PS and p16 status were prognostic factors for OS. Summary: Objectives: The optimal concurrent regimen, chemoradiotherapy (CRT) or bioradiotherapy (BRT), in locally advanced head and neck squamous cell carcinoma (LAHNSCC) remains controversial, especially in human papilloma virus-associated patients. Material and methods: Data of 265 patients with LAHNSCC treated with CRT (cisplatin, 100 mg/m 2 every 3 weeks, n  = 194) or BRT (weekly cetuximab, n  = 71), including 119 patients with known HPV/p16 status were analyzed. Results: Median follow-up was 54.5 months. The 5-year progression-free survival (PFS) and locoregional control (LRC) were 51.7% vs. 36.9% ( p  = 0.01) and 74.2% vs. 51.2% ( p  = 0.002), both in favor of CRT. Multivariate analysis adjusted for p16 status continued to show improved outcomes (PFS and LRC) for CRT. The 5-year LRC was significantly better with CRT vs. BRT both in the p16+ subgroup ( p  = 0.01) and in p16− or unknown subgroup ( p  = 0.02), and 5-year PFS was of non-significant trend of improvement with CRT vs. BRT in both subgroups ( p  = 0.07 in p16+ and p  = 0.09 in p16− or unknown, respectively). In the subset of oropharyngeal cancer patients with HPV/p16 status available ( n  = 88), MVA after adjusted for other clinical co-variates showed a non-significant trend of improvement of LRC with CRT compared with BRT (HR = 0.4, 95%CI, 0.1–1.0; p  = 0.06). Conclusion: Our long-term results suggested better outcomes in LAHNSCC patients receiving concurrent cisplatin over cetuximab regardless of HPV/p16 status.